Incidencia de la política de cobranzas en la liquidez de la empresa de transporte Transpesa S.A.C. - Galvez Marreros, Karen Graciela (2013)
The present research work: "IMPACT OF POLICY IN CASH COLLECTION OF TRANSPORT COMPANY TRANSPESA SAC " aims to raise awareness of how policy influences Collection in the company. In the development of this research used the descriptive method because the data were obtained by direct observation, as well as collects, selects and consolidates information. On the other hand, we also interviewed the head of the area of Finance, which is directly related to the research topic. The main objective of the study is to analyze the impact of policy on liquidity collections company Transpesa SAC Transport and describe the different policies that can be used for collection management. The conclusion I have reached is that the collection policies have not been implemented efficiently, as they have been unfavorable for obtaining liquidity of the company, so that the management of collections is not controlled or monitored, so which leads to not having timely information for decision making. Keywords: Collections Policy, Financing, Liquidity, slow payer.